Bayesian prediction of RNA translation from ribosome profiling - Malone, Brandon; Dieterich, Christoph (Nucleic acids research, 2017)
Abstract. Ribosome profiling via high-throughput sequencing (ribo-seq) is a promising new technique for characterizing the occupancy of ribosomes on messenger
Gesehen am 07.09.2018